Corporate value creation : - Karlson, Lawrence C. (Wiley, 2015)
This invaluable resource is filled with detailed information on financial statements, valuation, modeling and forecasting, and other aspects of essential business activities. The author includes a discussion of the best practices management needs to adopt if they are to successfully improve bottom-line productivity. Filled with illustrative examples, and comprehensive in scope, the book explores the basics of income statements, balance sheets, and cash flow statements. Then, using critical concepts like Weighted Average Cost of Capital, Karlson outlines the strategies and best practices for managing Return on Capital Employed. He also includes detailed discussions of pricing-driven models and defines the characteristics and attributes of several value-added models.